(untitled) (Ustozlar uchun, 2025)
Abstract Respiration is one of the most vital processes necessary for the survival of living organisms. This article provides a comparative analysis of the anatomical and physiological features of the respiratory systems in humans and animals. The mechanisms of respiration in mammals, birds, reptiles, amphibians, and fish are examined, highlighting their similarities and differences. The findings show that while the fundamental purpose of respiration is universal across species, its structural and functional adaptations vary depending on the habitat and evolutionary pressures. These differences play an essential role in understanding biological diversity and ecological adaptability.